Results of work of the maternal child program. University Pediatric Hospital of Cienfuegos, 2021 - Lairi García Ríos; Fernando de la Mora Martín; Milenys Acosta Fonseca; Antonio Masot Rangel; Claudia Beatríz Surí García (Medisur)
Background: A fundamental strategy to achieve satisfactory results in maternal and child care was the implementation of the National Program for Maternal and Child Care (PAMI). The results of the PAMI in 2021 are not what is expected each year at the country level and it was not far from the reality of the Paquito Glez University Pediatric Hospital. Objective: Mention the results of the work of the Maternal and Child Program at the University Pediatric Hospital of Cienfuegos in the year 2021. Methods: descriptive, cross-sectional study, carried out at the Pediatric Hospital of Cienfuegos and which includes the comprehensive results of the Maternal and Child Program at said institution. All the indicators of the program are exposed. It also offers a contextualization of the scenario in the year 2021. Results: The scenario of confrontation with COVID-19 in Cienfuegos had an impact during the year 2021 on the results obtained by the institution, increasing care in the emergency room to 45,151 consultations, as the main reason for Acute Respiratory Diseases. Hospital mortality increases by six more deaths compared to 2020, responding to the main cause of emergency care followed by Sepsis. The municipal seat remains the main issuer of patients and is followed in frequency by Cumanayagua and Rodas, corresponding to the municipalities that contribute the greatest number of admissions. The average hospital stay was 4.3 and the general survival behaves in 96.8%. Conclusions: The group of the institution continues to develop clinical management to achieve the quality of optimal hospital services to influence, modify and make sustainable the indicators with unfavorable results.